2017
DOI: 10.18203/2320-1770.ijrcog20170578
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and perinatal outcomes in cases of antepartum haemorrhage: a 3-year observational study in a tertiary care hospital

Abstract: Background: The leading cause of maternal mortality in world is obstetric haemorrhage. Antepartum haemorrhage (APH) is defined as bleeding from or into the genital tract after 28weeks of pregnancy and before delivery of the baby. The aim of the present study is to study the demographic profile, type of antepartum haemorrhage (APH), maternal and perinatal complications in cases of APH and to formulate preventive guidelines so as to reduce maternal and perinatal complications in cases of APH.Methods: The study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 2 publications
10
8
1
Order By: Relevance
“…The mean gestational age at delivery in present study was 35.22± 2.82 weeks and 60.1% of the patients in present study had preterm deliveries which was almost similar to studies conducted by Samal SK et al and Singhal S et al 14,15 This higher rate of preterm deliveries could be due to early decisions and surgical intervention in view of maternal health.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The mean gestational age at delivery in present study was 35.22± 2.82 weeks and 60.1% of the patients in present study had preterm deliveries which was almost similar to studies conducted by Samal SK et al and Singhal S et al 14,15 This higher rate of preterm deliveries could be due to early decisions and surgical intervention in view of maternal health.…”
Section: Discussionsupporting
confidence: 89%
“…Neonatal death rate was 8.6%, 11.5% cases were of IUD and these were most commonly seen with abruption followed by placenta previa. Results were similar to studies conducted by Singhal S et al and Maurya A et al, Chufamo N et al, calculated the perinatal mortality to be 36.9% while Arora R et al 10,15,19,25 reported very high mortality rate of 61.5%. The lower neonatal death in present study may be due better neonatal care facilities with well-equipped NICU at our institute.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations